Persepsi Siswa Mengenai Perilaku Seksual Pranikah dan Bimbingan yang Diperoleh di Sekolah - Herdinda Oktafani; Indah Sukmawati (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This research is motivated by the phenomenon that there are still students who do not understand premarital sexual behavior. It can be seen that there are students who hold hands with the opposite sex, there are students who are alone with the opposite sex in public places in school uniforms. The purpose of this study is to describe students' perceptions of premarital sexual behavior and describe the guidance obtained at school. The population in this study consisted of all X and XI grade students at SMK Negeri 1 Padang Panjang in the 2024/2025 school year, totaling 681 people. The research sample amounted to 253 students selected through stratified random sampling technique. Data collection was carried out by distributing instruments in the form of questionnaires measuring students' perceptions of premarital sexual behavior and guidance obtained at school. The results showed that (1) students' perceptions of premarital sexual behavior at SMK Negeri 1 Padang Panjang were generally in the good category (2) the guidance obtained at school was generally in the very good category. Based on the results of this study, counseling teachers can maintain and improve the quality of services that have been provided to prevent the emergence of premarital sexual behavior among students. This effort can be done through the provision of information services, individual counseling, and group guidance that specifically discusses topics regarding premarital sexual behavior.